Pengelolaan Sampah Berbasis Masyarakat: Revitalisasi Bank Sampah Syariah UIN Sunan Ampel Surabaya untuk Masa Depan yang Lebih Hijau - Fitrianto, Achmad Room; Nawangsari, Ajeng Tita; Agustin, Riska; Arista, Setia Rini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The inadequate management of waste in a region has adverse effects on environmental pollution in that area. The resulting impacts include a decline in health due to disease outbreaks carried by waste, disruptions to aesthetics and comfort, disturbance of ecosystems, and economic losses. Current waste management practices often lack the principles of reduction, reuse, and recycling, leading to negative effects on public health and the environment. Comprehensive and integrated waste management is needed to achieve economic benefits, health for the community, and environmental safety. This study focuses on the revitalization of a Sharia-based Waste Bank (BSS) at Sunan Ampel State Islamic University (UINSA) in Surabaya, Indonesia. The aim is to support the university's commitment to environmental sustainability and implement quality waste management. The research employs a combination of qualitative and quantitative methods, including surveys, focus group discussions, and interviews, to assess the current waste management situation, stakeholders' perceptions, and potential strategies for waste bank revitalization. The study proposes a community-based waste management model through the revitalization of BSS to empower both internal and external stakeholders. This model integrates educational programs, financial incentives, and technological solutions to promote waste reduction, sorting, and recycling. The research contributes to enhancing waste management practices in the university and its surrounding communities while aligning with global sustainability goals.